Biological and nutrient responses to catchment disturbance and warming in small lakes near the Alaskan tundra–taiga boundary. (October 2014) - Medeiros, Andrew S; Taylor, Derek J; Couse, Madeline; Hall, Roland I; Quinlan, Roberto; Wolfe, Brent B
Understanding effects of recent climate warming and changes in catchment conditions on nutrient cycling and the biology of shallow subarctic lakes is necessary to predict their evolution. Here, we use multiple analytical methods on sediment cores to identify effects of change in catchment conditions on nutrient availability and biotic assemblages in two subarctic lakes on the Seward Peninsula (Alaska, USA). We compare limnological and biotic responses to flooding and expansion of a thermokarst lake basin (late 1950s), increased shrub growth in the catchment of another lake (since the mid-1980s), and regional warming (since the late 1970s). Among these three environmental drivers, the largest biotic responses occurred because of flooding and expansion of the thermokarst lake. An increase in the nitrogen isotope composition and decline in organic carbon isotope composition in sediments are interpreted to reflect an elevated supply of dissolved inorganic carbon and nitrogen. This was associated with significant shifts in composition of chironomid and diatom assemblages. In contrast, increases in particulate organic carbon and nitrogen from enhanced shrub growth had less influence on the biota. Declines in cold-water biotic indicators typical of warming lakes in Arctic regions occurred several decades after catchment-induced changes to the nutrient supply in both systems. This indicates that initial lake catchment condition may mediate lake-specific changes in nutrient cycling and aquatic productivity within regions undergoing warming.